Keanekaragaman Kapang Patogen dan Non Patogen pada Imago, Kokon, dan Larva Instar Keenam Ulat Sutera Liar Attacus atlas (Lepidoptera: Saturniidae) - Agustin Indrawati; Damiana Rita Ekastuti; Erdina Pangestika; Reinilda Alwina (Jurnal Sain Veteriner, 2019)
Attacus atlas is one of several mould species in Indonesia known as kupu-kupu gajah. Information about variety of mould is rarely known. The purpose of this research was to obtain data about variety of pathogenic or non pathogenic mould at imago,cocoon, and sixth larvae phase of wild silkworm A. atlas. Mould was isolated from cocoon, integument, alimentary duct and reproduction duct of imago, trachea, midgut and hindgut, also haemolymph of larvae. Isolated mould was cultured on potato dextrose agar. Isolated mould from cocoon and imago was identified by macroscopic and microscopic observation. The results showed that there were two kind of moulds from cocoon which were Fusarium oxysporum  and Aspergillus flavus. There were four kind of moulds from imago A. atlas which were Aspergillus flavus, Aspergillus versicolor, Aspergillus fumigatus, Fusarium dimerum, and Aspergillus sp.There were three kind of moulds from sixth larvae which were Aspergillus fumigatus, Aspergillus flavus, and Fusarium dimerum. The mould which has opportunistic pathogenic for Attacus atlas were Fusarium oxysporum, Aspergillus  flavus, Aspergillus fumigatus and Fusarium dimerum.